Learning to think, perform and act with integrity: does teacher education have a signature pedagogy, and why does this matter? - Brooks, C; McIntyre, J; Mutton, T (UCL Press, 2023)
Unprecedented reform to teacher education in England, through the Initial Teacher Training Market Review, led to the threat of removal of the right for established providers to offer programmes of initial teacher education beyond 2024 without reaccreditation. Such policy reform has been constructed in relation to a perceived gap in research about knowledge of the best way to educate or train new teachers. Using Lee S. Shulman’s concept of signature pedagogies we consider the varying ways in which theoretical ideas are underpinned by common models of, and approaches to, teacher education pedagogy. We mobilise Shulman to analyse five models, which we categorise as ‘knowledge-first’ or ‘people-first’, to see the extent to which, if at all, there is a theoretically informed signature pedagogy for initial teacher education. Our analysis shows that there is no one discernible knowledge base or theory that underpins a signature pedagogy for teacher education, but a suite of possibilities about how a signature pedagogy of teacher education could be understood. Moreover, it is our contention that policy reform of initial teacher education based on econometric analysis fails to recognise the most important dimension of a signature pedagogy, learning how to act with integrity as a professional teacher.